A single-crystalline diamond X-ray detector based on direct sp3-to-sp2 conversed graphene electrodes. Issue 1 (31st December 2022) - Yuan, Qilong; Liu, Linyue; Dai, Dan; Zhou, Yuhong; Liu, Ying; Yang, Mingyang; Qiu, Mengting; Jia, Zhenglin; Li, He; Nishimura, Kazhihito; Tian, Geng; Chee, Kuan W. A.; et al.
Abstract: Diamond is an ultrawide bandgap semiconductor with excellent electronic and photonic properties, which has great potential applications in microelectronic and optoelectronic devices. As an allotrope of diamond, graphene also has many fantastic properties like diamond, which caught much attention in combing them together. In this work, a direct sp 3 -to-sp 2 conversion method was proposed to fabricate graphene layers on single crystal diamond by thermal treatment with Ni film catalyst. By optimizing the conversing conditions, a thin graphene layer with low sheet resistance was obtained on diamond. Based on this, an all-carbon sandwich structural graphene-diamond-graphene (GDG) detector was fabricated, which shows low dark current of 0.45 nA at 0.5 V μm −1 applied electric field. The maximum sensitivity of this detector is obtained when the incident X-ray is 12 keV, with the value of 2.88 × 10 −8 C Gy −1 . Moreover, the rise time and delay time of the GDG detector is about 1.2 and 22.8 ns, respectively, which are very close to that of diamond detector with Ti/Au electrode. The realization of the direct in-situ sp 3 -to-sp 2 conversion on diamond shows a promising approach for fabricating diamond-based all-carbon electronic devices.